Development of AKM (Minimum Competency Assessment) Instrument for Students' Financial Literacy on Money and Investment Material in Class XI IPS SMAN 1 Long Apari - Asnur, Rukdianti Aslinda; Widiartini, Ni Ketut; Sudirtha, I Gede (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The objectives to be achieved in this study are to design the AKM (Minimum Competency Assessment) instrument model of financial literacy of students of SMAN 1 Long Apari class XI IPS on Money and Investment Material. To test the quality of AKM (Minimum Competency Assessment) instrument of financial literacy of students of SMAN 1 Long Apari class XI IPS on Money and Investment Material. This research includes development research or R&D (Research and Developmet), with 4D development procedures (Define, Design, Developt and Deseminate). The research subjects were 3 classes at level XI IPS with a total of 70 students, which were divided into two trial groups, namely in the large group of 60 students obtained from 6 times the number of test items developed. While in determining the amount of test subjects in the small group in this study were 20 students. The data analysis used passed the content validity test stage, instrument validity, reliability, difficulty level and question differentiation. The results of data analysis show that this instrument has passed the test of content validity, instrument validity, reliability, difficulty level, and question differentiation. Thus, this financial literacy AKM instrument can be used as an effective tool to measure students' competency level in money and investment materials.